2010
DOI: 10.1105/tpc.109.070185
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis PCR2 Is a Zinc Exporter Involved in Both Zinc Extrusion and Long-Distance Zinc Transport

Abstract: Plants strictly regulate the uptake and distribution of Zn, which is essential for plant growth and development. Here, we show that Arabidopsis thaliana PCR2 is essential for Zn redistribution and Zn detoxification. The pcr2 loss-of-function mutant was compromised in growth, both in Zn-excessive and -deficient conditions. The roots of pcr2 accumulated more Zn than did control plants, whereas the roots of plants overexpressing PCR2 contained less Zn, indicating that PCR2 removes Zn from the roots. Consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 61 publications
4
136
1
1
Order By: Relevance
“…It has been shown that AtPCR1 expressing yeast cells take up less and that protoplasts isolated from antisense plants take up more cadmium, compared to control cells (Song et al, 2004). Similar observations were made for AtPCR2 expressing yeast cells, which also took up less zinc (Song et al, 2010). These results indicate that AtPCR1 and AtPCR2 act as heavy metal exporters.…”
Section: A B C E D Fsupporting
confidence: 68%
See 3 more Smart Citations
“…It has been shown that AtPCR1 expressing yeast cells take up less and that protoplasts isolated from antisense plants take up more cadmium, compared to control cells (Song et al, 2004). Similar observations were made for AtPCR2 expressing yeast cells, which also took up less zinc (Song et al, 2010). These results indicate that AtPCR1 and AtPCR2 act as heavy metal exporters.…”
Section: A B C E D Fsupporting
confidence: 68%
“…Microarray results on the tissue-specific expression of AtPCR1 and 2 are not reliable, since the sequence used for the microarray analysis present in the public databases does not distinguish between the two. Promoter-reporter gene constructs revealed that AtPCR1 is expressed in stems, leaves, flowers and siliques but not in roots (Song et al, 2010). In young leaves it is exclusively expressed in trichomes, while in older leaves, AtPCR1 is expressed in all cells, although the strongest signal is still present in trichomes.…”
Section: Identification and Properties Of Pcrsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other transporters can also perform the export of Zn to vascular tissues. In Arabidopsis, pcr2 lossof-function mutants accumulate Zn in roots, suggesting a role of in root-to-shoot translocation of Zn, independent of HMA2 and HMA4 (Song et al, 2010). Furthermore, it was proved that AtFRD3 is involved in loading Zn into xylem (Pineau et al, 2012).…”
Section: Zinc Uptake By Plantsmentioning
confidence: 99%